Bandar Bakau Tourism Object: The Efforts to Maintain Environmental Sustainability and Improve The Socio-Economic Community - Yoskar Kadarisman; Rina Susanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Bandar Bakau tourism is an initiative from the community, the local government, and the company. The research objective was to analyze and explain the effects of Bandar Bakau tourism on environmental, social, and economic sustainability. This research used a qualitative method with interview data collection techniques, observation, and documentation. Bandar tourism was well managed, which could provide benefits in maintaining land erodes from seawater so as not abrasion. In terms of the economy, it provided business opportunities and jobs for the surrounding society. This research could be a model of environmental management in coastal areas that integrated community initiatives and ecological and economic interests based on the active participation of all parties. Wisata Bandar Bakau merupakan inisiatif dari masyarakat, pemerintah daerah, dan perusahaan. Tujuan penelitian ini adalah untuk menganalisis dan menjelaskan pengaruh pariwisata Bandar Bakau terhadap kelestarian lingkungan, sosial, dan ekonomi. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Wisata bandar yang dikelola dengan baik, dapat memberikan manfaat dalam menjaga erosi tanah dari air laut agar tidak terjadi abrasi. Dari segi ekonomi memberikan peluang usaha dan lapangan pekerjaan bagi masyarakat sekitar. Penelitian ini dapat menjadi model pengelolaan lingkungan di wilayah pesisir yang mengintegrasikan inisiatif masyarakat dan kepentingan ekologi dan ekonomi berdasarkan partisipasi aktif semua pihak.